"This is England": migration and the colonial travel archive in Jean Rhys's Voyage in the Dark and George Lamming's The Pleasures of Exile. Issue 2 (4th May 2023) - Derby, Shannon
ABSTRACT : This essay pairs Jean Rhys with George Lamming to offer insight into the trajectory of migration from the Caribbean to England in the twentieth century. I focus on an aspect of their work that has received little scholarly attention: allusions to Richard Hakluyt's accounts of English exploration and imperial expansion in Jean Rhys's autobiographical novel, Voyage in the Dark (1934) and George Lamming's collection of personal essays, T he Pleasures of Exile ( 1960). Through a reading that focuses on Rhys's and Lamming's intertextuality with Hakluyt as well as their narrative focus on migration to England, I situate their texts in conversation with historic and modern forms of travel literature. I argue that Rhys and Lamming deploy references to narratives of imperial expansion to (1.) call attention to the historical mobilities upon which their travels from the West Indies to England are predicated; and (2.) reverse the formula of the colonial travel narrative – accounts of travel from the imperial "center" to the colonial "periphery" that frames the latter as exotic spaces to be domesticated – to articulate a modern state of the collapsing, as opposed to expanding, English empire.